The influence of product characteristics on online purchase intention among white collar workers - Osman, Syuhaily; Yap, M. C. (Institut Sosial Malaysia, 2011)
The study examined the influence of product characteristic on online purchase intention among white-collar workers in Petaling Jaya. A simple random sampling method was used to select the private companies in Petaling Jaya and the respondents (i.e., the staffs in the particular companies) were then selected via convenience sampling. This sampling strategy was chosen because it requires minimum involvement from the companies, and it was also the most practical and appropriate strategy for the present study. The data were collected using self-administered questionnaire. SPSS and hierarchical multiple regression were used to determine the most influential product characteristic which may influence the online purchase intention. Results indicated that more than half of the respondents had high level of online purchase intentions and they were more willing to make purchases in internet store in future. The result of multiple regression analysis showed that low cost, frequently purchased and intangible products had significant influences on online purchase intention ((3= 0.295, p<0.01).